Mechanization in Harvesting and Post-Harvest Operation for Paddy in Konkan Region and Its Economic Feasibility - BHANAGE, G. B.; SHAHARE, P. U.; DESHMUKH, P. S.; GAIKWAD, P. B.; AWARE, V. V. (Journal of the Indian Society of Coastal Agricultural Research, 2016)
Rice is primarily a wetland crop and major staple food in Konkan region of Maharashtra state. For rice production the various operations are done manually. The agricultural operations are laborious and require huge manpower. It involves lot of drudgery. The scarcity of labours in these days is resulting into delay in harvesting and threshing operation. The increase in labour cost is resulting into paddy production uneconomical. In order to improve the mechanization status of Konkan region, feasibility of harvesting and threshing machines was studied and operating cost was determined. The different combinations were studied i.e. serrated sickle, pedal operated thresher and hand operated winnower as C-1; sickle, pedal operated thresher (wire loop type) and power operated winnower as C-2; self-propelled reaper, pedal operated thresher (wire loop type) and hand operated winnower as C-3; self-propelled reaper, power operated thresher (wire loop type) and power operated winnower in C-4, self-propelled reaper and inverted chain conveyor thresher (DBSKKV design) as C-5; reaper binder and power operated thresher (wire loop type) and power operated winnowing fan as C-6; reaper binder and inverted chain conveyor thresher (DBSKKV Design) as C-7; reaper binder and axial flow thresher as C-8 and combine harvester as C-9. It was found that, the major factor in the cost analysis of the machineries was the variable cost and capacity of the machine. These two factor affects directly on the total cost of operation of the machinery per ha. The majority of farmers (0.2 ha land holders) cannot procure the machines for harvesting, threshing and winnowing due to higher cost of machine and the socio economic status of farmers. The use of reaper and reaper binder can be suitable for the marginal and medium farms in Konkan region. The combinations of machinery involves reaper, reaper binder, power operated wire loop thresher, inverted chain conveyor thresher hand, operated winnowing fan and power operated winnowing fan finds potential in Konkan region. In order to get benefit of mechanization to majority of farmers, the custom hiring services and implement bank schemes needs to promote on massive scale.